Proceeding Book 1 Simposium dan Workshop: Continuing profesional development on clinical pathology and laboratory medicine (CPM_CPLM) JogloSemar X - Banundari Rahmawati (Joglo Semar Patologi Klinik, 2018)
Proceeding Book 1 Simposium dan Workshop: Continuing profesional development on clinical pathology and laboratory medicine (CPM_CPLM) JogloSemar X